Effect of riveting parameters on the quality of riveted aircraft structures with slug rivet - Changyi Lei; Yunbo Bi; Jiangxiong Li; Yinglin Ke (Advances in Mechanical Engineering, 2017)
Slug rivet should be installed by automatic drilling and riveting machine due to its special structure. The investigation on slug rivet is limited. In order to promote the application of slug rivet, this article conducts investigations on slug rivet installation process. For the understanding of the riveting quality of a riveted lap joint, it is essential to analyze the riveting parameters. There are numerous parameters associated with a riveting process such as squeezing force, rivet structure, countersunk hole structure, hole diameter, sheet thickness, and clamping force. Incorrect selection or variations in these parameters could directly affect the riveting quality. The aim of this article is to study the impact of the aforementioned parameters on the riveting quality of a riveted aircraft structure. The interference condition is considered as the main quality control criterion. The squeezing force is introduced as the most important parameter for the riveting quality. The study provides a deeper understanding of the slug rivet installation process with the impacts of its riveting parameters. This study will pave the way for further researches and extend the scope of the slug rivet application to more structural connections.